Jeanne d’Arc: Was There a Prophet? Reflections on the Book of O. Togoyeva “The Heretic, who Became Holy” - O. I. Nuzhdin (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
This article is devoted to the analysis of the concept of O. I. Togoeva, proposed by her as a research method in the monograph «The heretic, who became holy». In it, the author attempted to prove that the national heroine of France, Jeanne d’Arc, was a visionary, a prophet who had predicted individual events of the Hundred Years War. Since contemporaries were not sure who its prophecies come from - from God or from the Devil, we had to perform several procedures using the «discretio spirituum» method, that is, the « discerning of spirits». The first two, held in Chinon and in Poitiers in the spring of 1429, ended with the acquittal of Joan of Arc, the third, completed in Rouen in 1431, with an accusation, and finally, the last - in 1450-1456, - restoration of a good name. One may agree that some contemporaries considered Joan of Arc as a prophet or presented her as a prophet, but the fact that the Maid of Orleans really was a prophet remained unproved. The article shows that other interpretations of the mission of Joan of Arc and her actions are possible, including an explanation of her actions not as a prophet, but as one of the captains of the royal army.